2009
DOI: 10.3348/kjr.2009.10.5.481
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Mortality after Emergent Transjugular Intrahepatic Portosystemic Shunt Placement: Use of APACHE II, Child-Pugh and MELD Scores in Asian Patients with Refractory Variceal Hemorrhage

Abstract: ObjectiveThis study was designed to determine if existing methods of grading liver function that have been developed in non-Asian patients with cirrhosis can be used to predict mortality in Asian patients treated for refractory variceal hemorrhage by the use of the transjugular intrahepatic portosystemic shunt (TIPS) procedure.Materials and MethodsData for 107 consecutive patients who underwent an emergency TIPS procedure were retrospectively analyzed. Acute physiology and chronic health evaluation (APACHE II)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 17 publications
4
24
1
Order By: Relevance
“…Most of the reports found in the literature show a follow-up shorter than this study's which was during a 12-year period, being observed only two long term studies of 10-year followup (27,28) . This study shows early death occurrence in 19 (26.4%) patients and global mortality of 41 (60.3%) patients.…”
Section: Discussioncontrasting
confidence: 58%
See 3 more Smart Citations
“…Most of the reports found in the literature show a follow-up shorter than this study's which was during a 12-year period, being observed only two long term studies of 10-year followup (27,28) . This study shows early death occurrence in 19 (26.4%) patients and global mortality of 41 (60.3%) patients.…”
Section: Discussioncontrasting
confidence: 58%
“…This study shows early death occurrence in 19 (26.4%) patients and global mortality of 41 (60.3%) patients. Thus, global mortality rate is similar to or inferior when compared to long term studies as Yoon et al (28) (58.9%) and Tzeng et al (27) (77%). Yet, early mortality which independs on the follow-up period presents similar rating to those shown in literature as in Zhuang et al (30) (22.3%), Chalasani et al (5) (23.2%), Tzeng et al (27) (28%).…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…We also evaluated the possible correlation between outcomes and various clinical and laboratory parameters and severity scores. The severity scores evaluated for mortality were Child-Pugh (CP) [11], Model for End-Stage Liver Disease (MELD) [12], Model for End-Stage Liver Disease-Na (MELD-Na) [13], SOFA, and Acute Physiology and Chronic Health Evaluation II (APACHE II) [14]; these were all calculated within 48 h of admission. Furthermore, the presence of positive systemic inflammatory response syndrome (SIRS) criteria at admission was also correlated with patients' outcome.…”
Section: Methodsmentioning
confidence: 99%